2021
DOI: 10.1002/mabi.202000386
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Controlled Adhesion to Carbohydrate Functionalized Microgel Films: An E. coli and Lectin Binding Study

Abstract: The preparation of thermoresponsive mannose functionalized monolayers of poly(N‐isopropylacrylamide) microgels and the analysis of the specific binding of concanavalin A (ConA) and E. coli above and below the lower critical solution temperature (LCST) are shown. Via inhibition and direct binding assays it is found that ConA binding is time‐dependent, where at short incubation times binding is stronger above the LCST. Given larger incubation times, the interaction of ConA to the microgel network is increased be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In comparison to macroscopic polymer gels, microgels show a range of interesting properties, such as rapid and strong volume changes upon temperature variation, narrow size distribution, and straightforward processing toward coatings. [15][16][17][18] In addition, their synthesis via free radical polymerization is comparatively simple. Such microgels are often composed of polymers with an LCST in the physiological temperature range, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to macroscopic polymer gels, microgels show a range of interesting properties, such as rapid and strong volume changes upon temperature variation, narrow size distribution, and straightforward processing toward coatings. [15][16][17][18] In addition, their synthesis via free radical polymerization is comparatively simple. Such microgels are often composed of polymers with an LCST in the physiological temperature range, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The microgel coatings were prepared on silanized hydrophobic glass surfaces in order to facilitate firm binding of the microgel with the surface. Previous work on PNIPAM microgel coatings in hydrophobic plastic dishes confirmed that binding is persistent after mechanical agitation, rinsing, etc . To form a monolayer of microgels, simple drop-casting deposition was employed followed by drying and washing to remove excess microgels .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous work on PNIPAM microgel coatings in hydrophobic plastic dishes confirmed that binding is persistent after mechanical agitation, rinsing, etc. 53 To form a monolayer of microgels, simple drop-casting deposition was employed followed by drying and washing to remove excess microgels. 47 A surface fully covered with a microgel dispersion at a concentration of 10 μg ml −1 or higher will lead to densely packed monolayers (Figure 2).…”
Section: Microgel Surface Coatingsmentioning
confidence: 99%
“…binding receptor FimH at their fimbriae, which enables their attachment to cells. 14,16,29,30,40 Here, we studied the E. colimicrogel aggregation via optical microscopy and visual inspection as a measure of specific microgel interactions (Figure 2). To study the effect of microgel collapse and the concurrent increase in Man density in the network, the experiments were conducted below and above the VPTT, at 20 and 37 °C.…”
Section: Study Of Man-mediated Binding By Clustering Between Microgel...mentioning
confidence: 99%
“…Therefore, three main parameters controlling the specific binding under microgel phase transitions are investigated: crosslinking, type of polymer backbone, and ligand hydrophobicity (Figure ). For example, previous work on Man-decorated microgels showed selective binding and clustering of Escherichia coli above the VPTT, but a release of the bacteria was not possible below the VPTT. ,, We suggest that an increased shift in ligand density upon crossing the VPTT via reduced crosslinking could solve this problem. ,, Therefore, E. coli binding to Man presenting microgels with- and without a dedicated crosslinker (self-crosslinked) will be compared here.…”
Section: Introductionmentioning
confidence: 98%